Bacteriological profile and antibiotic susceptibility pattern of common isolates of neonatal sepsis, Ho Municipality, Ghana-2016 - Fortress Yayra Aku; Patricia Akweongo; Kofi Nyarko; Samuel Sackey; Fredrick Wurapa; Edwin Andrew Afari; Donne Kofi Ameme; Ernest Kenu (Maternal Health, Neonatology and Perinatology, 2018)
Abstract Background Globally, 4 million neonates die annually, with one-third of such deaths occurring as a result of infections. In 2011, there were 7.2million deaths in children below 5 years globally, and a proportion of 40% of these deaths occurred in neonates. Sepsis was reported to account for one-third of these deaths. Presently, multidrug antibiotic resistance is rapidly increasing in Neonatal Intensive Care Units (NICUs), particularly in developing countries and poses a threat to public health. The change in these organisms has been reported to vary across regions, between health facilities and even within the same facility. Continuous surveillance is required to inform antibiotic choice for neonatal sepsis management. We identified the common causative organisms of neonatal sepsis and their antibiotic susceptibility pattern in the Ho municipality. Method A cross sectional study was conducted in the Ho municipality from January to May, 2016. A semi-structured questionnaire was used to collect socio-demographic data from mothers of neonates with clinically suspected of sepsis. Clinical data of both mothers and neonates were extracted from case notes. A 2 ml volume of blood was also taken from neonates and dispensed into a 20 ml mixture of thioglycollate fluid broth and tryptone soy broth for culture and antibiotic susceptibility pattern determined. Results Out of the 150 clinically suspected neonatal sepsis cases, 91 (60.7%) were males. The Median gestational week was 38 (IQR: 36–39) and Median birthweight was 3.0 kg (IQR 2.5–3.4). The prevalence of culture positive sepsis was 17.3% of the 150 suspected cases. A total of 26 different pathogens were isolated, of which gram positive organisms had a preponderance of 18 (69%) over gram negative organisms 8 (31%). Staphylococcus epidermidis was the most common 14 (53.8%) isolate identified. There was a single isolate (4%) each of Proteus mirabilis and Escherichia coli identified. All the isolates identified showed 100% resistance to ampicillin. Conclusion The prevalence of culture proven sepsis was 17.3% and Staphylococcus epidermidis was the most common isolate identified. Pathogens isolated were resistant to the first line drugs for management of neonatal sepsis. Hence, the need for a review of first line drug for empirical treatment in neonatal sepsis.